A distributed algorithm to maintain a proximity communication network among mobile agents using the Delaunay triangulation. (July 2021) - Schwab, Alexander; Lunze, Jan
Abstract: This paper addresses the maintenance of a communication network in which mobile agents are connected to their nearest neighbours. While all agents are able to move individually, the geometrical relation to each other changes along their trajectories. The main idea is to develop distributed algorithms which enable the agents to monitor and to switch communications links in real time so that the overall network topology equals a Delaunay triangulation at any time. It is shown which information has to be stored locally by each agent and exchanged among the agents via digital communication. The paper closes with an experimental evaluation of the proposed methods.